Proposal for a pedagogical intervention in EPT: the problem of waste electrical and electronic equipment (Research, Society and Development, 2022)
The growing use of electronics associated with the rapid obsolescence of these goods, generates, proportionally, the accumulation of waste, also called “technological waste”. By improperly disposing of these products, in addition to wasting raw material that is already scarce on the planet, it also compromises environmental health. Based on this assumption, the objective of this work is to present a proposal for a pedagogical intervention at the heart of the problem of the final destination of Waste Electrical and Electronic Equipment (WEEE), from Reverse Logistics (LR), using strategies of Environmental Education (EA). For this, the approach of interdisciplinarity and transversality, in the environment of Vocational and Technological Education (EPT), outlines the methodological path, reaching the structuring axes Environment, Health and Safety, as well as Technological, Information and Communication. The qualitative approach, exploratory objective and bibliographic procedures were used as research typology. However, the propositions presented here may reflect on the learning process, which is complex, continuous and challenging, and on the training of professionals who meet the demands of contemporary society.